Environmental variability and krill abundance in the central California current: Implications for ecosystem monitoring - Dorman, Jeffrey G.; Sydeman, William J.; Thompson, Sarah Ann; Warren, Joseph D.; Killeen, Helen J.; Hoover, Brian A.; Field, John C.; Santora, Jarrod A. (Frontiers in Marine Science, 2023)
Krill are a direct conduit between primary productivity and recreationally and commercially important higher trophic level species globally. Determining how krill abundance varies with temporal environmental variation is key to understanding their function in coastal-pelagic food webs, as well as applications in fisheries management. We used nine years (2012–19 and 2021) of late spring/early summer hydroacoustic-trawl survey data in the California Current Ecosystem (CCE), coupled with new target strength models of two krill species (Euphausia pacifica and Thysanoessa spinifera), to investigate how adult krill biomass varied during a decade of unusual ocean climate variability. We estimate a mean biomass of 1.75–2.0 million metric tons on the central and northern California continental shelf. Overall, relative krill biomass was ~30% lower during 2015 and 2016, corresponding to a major warming event, and ~30% higher in 2013 and 2018, years of exceptionally strong upwelling. Variation in biomass was related to the prior year’s environmental conditions derived from our seasonal Multivariate Ocean Climate Index (MOCI), and E. pacifica and T. spinifera showed similar covariation during the study period. Biomass co-varied at different spatial scales and across sampling devices, suggesting that multiple indicators of abundance (and dispersion) are available and should be applied in ecosystem monitoring and modeling of krill and krill-dependent predators in the California Current ecosystem.